From Islamicizing the sciences to strategizing for Muslims’ scientific breakthrough - Adebayo, Rafiu Ibrahim (Universiti Kebangsaan Malaysia, 2015)
At inception, science and religion were seen as poles apart and so science was vehemently kicked against by religious leaders. Islam later came to bridge the gap between religion and science only to be later hijacked by the Western world and so science was rewritten from a purely materialist point of view; hence, experts in modern science became over-confident and arrogant to have relegated religion to the lowest ebb and looked down upon any knowledge which could not be scientifically proved. However attempts are being made to reconcile religion and science by Muslim reformers. These attempts are not without their shortcomings, hence the need for Islamization of the sciences for them to conform to the Islamic principle of unity of knowledge. However, the present researcher feels that there should be a step forward from the contemporary approaches to Islamicizing the sciences in form of colouring the Western scientific discoveries Islam, to making their own scientific breakthroughs, the type which immortalized Muslim scientists of the Islam’s golden ages. Without this, Muslims will continue to be mere consumers of the Western products. The strategy for the Ummah to achieve this is suggested in this paper.